"I Can Share Politics But I Don't Discuss It": Everyday Practices of Political Talk on Facebook. (December 2017) - Mascheroni, Giovanna; Murru, Maria Francesca
The article explores how a group of young people in Germany, Italy, and the United Kingdom experience and manage informal political talk on Facebook. Based on 60 interviews with 14- to 25-year-olds with diverse interest and participation in politics, it understands political talk as a social achievement dependent on the situational definition, shaped by the perceived imagined audiences, shared expectations, and technological affordances. Results show that young people construct different interactional contexts on Facebook depending on their political experiences, but also on their understanding of the affordances of networked publics as shaped by the social norms of their peer groups. Many youth define Facebook as an unsafe social setting for informal political discussions, thus adhering to a form of "publicness" aimed at neutralizing conflicts. Others, instead, develop different forms of "publicness" based on emergent communicative skills that help them manage the uncertainty of social media as interactional contexts.